Young Milton the emerging author, 1620-1642 - Jones, Edward, 1950- (Oxford : Oxford University Press, 2012)
The experimental and diverse writing of John Milton's early career offers tanatalising evidence of a precocious and steadily ripening author. This book explores these writings, including 'Lycidas' and 'The Passion'.
Description based on online resource; title from home page (viewed on Jan. 4, 2013).
Includes bibliographical references and index.
Keywords: Milton, John, -- 1608-1674 -- Criticism and interpretation